SCAN-NF : a machine learning system for invoice product trasaction classification through short-text processing - Silva, Diego Santos da (2022)
Dissertação (Mestrado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2022.